Development of UNO-Litera Card Integrated Wordwall for Elementary Paragraph Writing Skills - Nur Ilmi; Febri Annisa; Wawan Krismanto (International Journal of Learning Reformation in Elementary Education, 2026)
Developing paragraph writing skills in elementary students requires innovative, interactive, and technology-integrated learning media. This study aimed to develop an UNO-Litera card integrated with Wordwall to facilitate paragraph writing skills in elementary school. The study employed a Research and Development (R&D) design using the 4D model, involving expert validation and limited field trials with grade 4 students and a classroom teacher. The developed media consists of printed word cards combined with a digital Wordwall unjumble game. The validity test results indicated that the product was very valid, while practicality tests showed that the media was very practical based on teacher and student responses. These findings suggest that the UNO-Litera card integrated with Wordwall is feasible for paragraph writing instruction and offers potential contributions to interactive literacy learning in elementary education.